Pulsed laser deposition of tin-doped indium oxide (ITO) on polycarbonate - YONG, T; TOU, T; TEO, B (2005)
Indium tin oxide (ITO) films were deposited on polycarbonate (PC) substrates in oxygen at room temperature by pulsed laser deposition (PLD) using a Nd:YAG laser with 355 and 532 nm wavelengths. The ITO films were analyzed by the four-point probe technique, atomic force microscopy (AFM) and UV-visible-Near IR spectrophotometry for electrical conductivity, surface morphological and optical transmission properties, respectively. The main plume species were identified by using a fiber optic spectrometer, which showed that the emission intensity produced by the 355 nm laser wavelength was considerably stronger than that produced by the 532 nm laser wavelength. The ITO film resistivity was an order of magnitude higher than that achieved by a KrF excimer laser, but comparable to ITO-coated substrates prepared by the sputtering method. (c) 2005 Elsevier B.V. All rights reserved.